Thailand : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2019)
This Financial System Stability Assessment paper on Thailand highlights that assets of the insurance and mutual fund sectors have doubled as a share of gross domestic product over the last decade, and capital markets are largely on par with regional peers. The report discusses significant slowdown in China and advanced economies, a sharp rise in risk premia, and entrenched low inflation would adversely impact the financial system. Stress tests results suggest that the banking sector is resilient to severe shocks and that systemic and contagion risks stemming from interlinkages are limited. Financial system oversight is generally strong, but the operational independence of supervisory agencies can be strengthened further. The operational independence of supervisory agencies can be strengthened further by reducing the involvement of the Ministry of Finance in prudential issues and ensuring that each agency has full control over decisions that lie within its areas of responsibility.